2014
DOI: 10.1177/1470320313495910
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme insertion/deletion gene polymorphisms is associated with risk of glioma in a Chinese population

Abstract: Introduction:The insertion/deletion (I/D) polymorphism of the angiotensin-converting enzyme (ACE) gene has recently been linked to the pathogenesis and progression of human cancers. The aim of this study was to evaluate the potential association between ACE I/D polymorphism and glioma in a Chinese population. Materials and methods: A case-control study involving patients with 800 glioma and 800 controls was conducted. Polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP) assay was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…In another study, Lian et al . suggested the insertion/deletion (I/D) genetic variant of the ACE gene as a risk biomarker for glioma, and performed a case-control study in a Chinese population, which showed that glioma patients had a significantly higher prevalence of the ACE DD-genotype detected in blood [ 51 ]. The AGT rs5050 is so far the only RAS component that is simultaneously related to prognosis and identified by a blood test, which would be both valuable and practical features for a biomarker in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Lian et al . suggested the insertion/deletion (I/D) genetic variant of the ACE gene as a risk biomarker for glioma, and performed a case-control study in a Chinese population, which showed that glioma patients had a significantly higher prevalence of the ACE DD-genotype detected in blood [ 51 ]. The AGT rs5050 is so far the only RAS component that is simultaneously related to prognosis and identified by a blood test, which would be both valuable and practical features for a biomarker in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…For the association between ACE I/D polymorphism and glioma, four studies including 1110 cases and 2335 controls were included for the analysis. Overall, the meta-analyses demonstrated no 8 China Chinese 800/800 Healthy subjects Pandith et al 9 India Indian 112/141 Healthy subjects Benenemissi et al 10 Algeria Algerian 36/195 Healthy subjects significant association between ACE I/D polymorphism and glioma risk. As shown in Figure 2(a), compared with ACE ID/II genotype, subjects with DD genotype showed a non-significant risk for glioma (OR 1.96; 95%CI 0.73 to 5.27; p = 0.18).…”
Section: Quantitative Analysis Resultsmentioning
confidence: 98%
“…16 Recently, Pandith et al 9 reported that ACE DD genotypes were highly presented in glioma cases 26.8% versus 10.6% in controls and conferred 5-fold risk for predisposition in glioma cases. Lian et al 8 also found that glioma cases had a significantly higher frequency of DD genotype than controls. Benenemissi et al 10 reported that ACE DD genotype was highly presented in glioma cases than controls and conferred 3.64-fold risk for predisposition in glioma cases compared with ID genotype.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations